(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2011)
Key words: CKD patients; Renam status at maiden presentation; Nephrology ward of CMCH DOI: 10.3329/jcmcta.v21i2.7729 Journal of Chittagong Medical College Teachers’ Association 2010: 21(2):7-10